KONSEP PENDIDIKAN ETIKA SUFISTIK-FILOSOFIS AL-GHAZÂLÎ - Sahid HM (Ulumuna, 2011)
Abstract: The study focuses on the ethic concept of al-Ghazâlî in education. The approach used by al-Ghazâlî, in relation to the educational ethic, is sufistic-philosopichal which tends to the concept of ma‘rifat Allâh, taqarrub, and tahassub through riyâdlah. These three dimentions are the main basis of how to educate the moslem’s ethic. For those whose spiritual has not been good yet, they are suppossed to learn constantly. Therefore, an educator may guide and bring spiritually the students to be close to Allah. In fact, al-Ghazâlî’s concept of ethic in education by sufistic-philosopichal approach has theoretically and practically broad influences for the moslem life all over the world. Such two influences indicate that practically and theoretically al-Ghazalî’s school of thought in ethical education turns out to be the basic of further thinking. Thus, the very strong al-Ghazalî’s influence toppled down the sufism at that time. Abstrak:  Kajian ini membahas konsep pendidikan etika al-Ghazâlî. Pendekatan yang digunakan oleh al-Ghazâlî dalam membina etika bermuara pada sufistik-filosofis yang cenderung pada ma‘rifat Allâh dan diproses dengan metode tazkîyat an-nafs, taqarrub, dan tahassub dengan cara riyâdlah. Tiga dimensi ini menjadi landasan untuk membina etika seseorang secara baik. Bagi seseorang yang jiwanya belum bersih, dia harus berguru dan minta petunjuk. Dengan demikian, guru dapat memberi petunjuk dan mengantarkan seorang murid sampai kepada Tuhan. Dalam perkembangannya, konsep pendidikan etika sufistik-filosofis al-Ghazâlî berpengaruh di belahan dunia baik secara teoritik maupun praktis. Dua pengaruh ini menggambarkan pemikiran al-Ghazâlî secara teoritis-praktis dalam bidang pendidikan etika. Pengaruh al-Ghazâlî yang sangat kuat mampu menumbangkan aliran tasawuf yang berlaku pada saat itu.